Mapping recombination rate on the autosomal chromosomes based on the persistency of linkage disequilibrium phase among autochthonous beef cattle populations in Spain - Mouresan, Elena Flavia (2019)
Fil: Mouresan, Elena Flavia. Universidad de Zaragoza. Departamento de Anatomía, Embriología y Genética Animal. Zaragoza, España.